Advances and challenges about Ni-based dual functional materials for alternating cycles of CO2 storage and in-situ hydrogenation to CH4 - Xinyue Su; Laihong Shen (Carbon Capture Science & Technology)
The utilization of dual functional materials (DFMs) in integrated CO2 capture and utilization (ICCU) has been attracted increasingly attention, with the conversion of CO2 to CH4 through the Sabatier reaction offering significant thermodynamic benefits. Ni, recognized for its catalytic efficiency among transition metals due to its cost-effectiveness and natural abundance while Ni-based DFMs have been favored to promote the conversion of CO2 to value-added chemicals. In the past decades, significant efforts have been dedicated to developing more efficient Ni-based catalysts to enhance CO2 conversion and CH4 selectivity. This study researched the thermodynamic and kinetic aspects of ICCU and summarized the recent industrial process at first. Then, an overview of the advancements in Ni-based DFMs, including synthesis methods, support materials and promoters were provided. Next, the mechanisms of CO2 methanation were also briefly addressed to provide a comprehensive understanding of the process. Finally, the future prospects were guided the development and application scenarios of Ni-based DFMs in the ICCU.